Theoretical Foundations of Preparing Students for Family Life - Umedjanova Malika Lukmanovna (European International Journal of Pedagogics, 2025)
The family and family upbringing play a vital role in achieving this goal. The family is a social necessity, a crucial link, and a pillar of both society and the state. Today, the issue of family upbringing and the preparation of students for family life is considered a pressing and significant socio-pedagogical problem in national education.